Factors affecting meat texture from Nellore and crossbreed Limousin-Nellore steers - Heinemann, Riana Jordão Barrozo; Pinto, Marcos Franke; Romanelli, Pedro Fernando (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate factors affecting meat texture from Nellore and crossbreed Limousin-Nellore steers. Fifty steers, 25 Nellore and 25 Limousin-Nellore, were randomly divided in five groups of 10 animals (five from each genetic group) and serially slaughtered during 204 days. Meat temperature and pH data were monitored during 24 hours post mortem. After this, fat thickness and rib area were measured. Longissimus dorsi muscle was removed to quality evaluation before and after 14 days ageing period. Crossbreed animals rib areas were higher. Fat thickness and marbling values from both genetic groups were similar. Live slaughter weight and fat content affected decrease of pH and temperature, but didn't result in difference in shear force. Crossbreed animals the most tender meat. Ageing process was responsible for 30% reduction in shear force, so this was, associated to genetic group, was the principal factor affecting meat texture.